Chemotherapy for unresectable and recurrent intramedullary glial tumours in children - Doireau, V (Nature Publishing Group, 1999)
Adjuvant treatment for intramedullary tumours is based on radiotherapy. The place of chemotherapy in this setting has yet to be determined. Between May 1992 and January 1998, eight children with unresectable or recurrent intramedullary glioma were treated with the BB SFOP protocol (a 16-month chemotherapy regimen with carboplatin, procarbazine, vincristine, cyclophosphamide, etoposide and cisplatin). Six children had progressive disease following incomplete surgery and two had a post-operative relapse. Three patients had leptomeningeal dissemination at the outset of chemotherapy. Seven of the eight children responded clinically and radiologically, while one remained stable. At the end of the BB SFOP protocol four children were in radiological complete remission. After a median follow-up of 3 years from the beginning of chemotherapy, all the children but one (who died from another cause) are alive. Five patients remain progression-free, without radiotherapy, 59, 55, 40, 35 and 16 months after the beginning of chemotherapy. The efficacy of this chemotherapy in patients with intramedullary glial tumours calls for further trials in this setting, especially in young children and patients with metastases. © 1999 Cancer Research Campaign